Bleeding Complications from Transesophageal Echocardiography for Liver Transplantation: A Systematic Review. (December 2022) - Dunkman, W. Jonathan; Williams, David A.; Manning, Michael W.
Transesophageal echocardiography (TEE) for liver transplant has historically been avoided due to concern it may cause bleeding from esophageal varices. However, several recent studies, as well as increasing clinical experience, have indicated that it may be safe in many circumstances. We performed a systematic review of the literature to identify and summarize studies reporting complications in patients having TEE during liver transplant. Studies were identified by searching relevant key terms on PubMed as well as citation searching in relevant reviews. We identified 6 studies between 1996 and 2015 which evaluated complications of TEE during liver transplant. They reported an overall bleeding complication rate between .3% and 2.8% and a major bleeding complication rate between .0% and .8%. Most of the major bleeds had identifiable high-risk features such as recent variceal bleeding or banding. Review of the literature suggests that TEE may be safely used in patients undergoing liver transplantation, even with known varices, with a complication rate similar to that of all patients undergoing TEE. However, the risks of TEE may outweigh the potential benefits among patients undergoing liver transplant with particular high-risk features.